Equine Infectious Anemia: seroprevalence in the northeastern region of Argentina - Espasandin, A.G.; Vissani, Maria Aldana; Martinez, D.E.; Lottero, E.; Carballo, L.P.; Storani, C.A.; Jacobo, R.A.; Cipolini, M.F. (2017)
The goal of the present work was to determinate the prevalence of EIA infection among work horses in three cattle farms situated in the Northwest of Corrientes. A sample of whole blood was obtained from all the horses (n¼212), and the AGID test was carried out. One hundred and nineteen horses were found infected (AGID positive)